A girl named Anna (Toronto, Ontario MIRA Books, 2019)
"Raised in a quiet rural community, Anna has always been taught that her mamma's rules are the only path to follow. But, on her 18th birthday, she defies her mamma for the first time in her life and goes to Astroland. She's never been allowed to visit Florida's biggest theme park, so why, when she arrives, does everything about it seem so familiar? And is there a connection to the mysterious letter she receives that same day--a letter addressing her by a different name?"--Publisher's description.
Ages 17+